STRATEGIC MANAGEMENT ANALYSIS OF PT XYZ ONE OF INDONESIA'S FAST GROWING FOOD AND BEVERAGE COMPANIES - Fritza Difa; Muhammad Nadhif Said; Muhammad Ivan Farrel; Tiara Puspa (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
PT XYZ operates in Indonesia’s competitive food and beverage industry and faces operational challenges, including inconsistent product quality, long customer queues, and service inefficiencies. This study aims to identify the most appropriate strategy to improve operational performance and sustain competitive advantage using Fred R. David’s strategic management framework. The analysis employs the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Competitive Profile Matrix (CPM), SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM). The results indicate that PT XYZ has strong internal capabilities (IFE = 2.83), responds effectively to external conditions (EFE = 3.20), and maintains a strong competitive position within the industry (CPM = 3.40). Based on the QSPM analysis, Strategy II focusing on product standardization, queue management, and service quality improvement achieved the highest Total Attractiveness Score (TAS = 3.63). Therefore, operational improvement is recommended as the company’s primary strategic priority to enhance customer satisfaction and support sustainable business growth.